Development of Corporate Social Responsibility and Company Social Reporting - Inna Berzhanir; Anatolii Berzhanir; Tetiana Yashchuk; Oleksandr Kirdan; Nataliia Pacheva (Communications of International Proceedings, 2020)
The formation of a modern market economy presupposes the functioning of a business aimed at increasing the return on invested capital, the implementation of a strategy for improving working conditions and personnel development, cooperation with local authorities, solving environmental problems. The immediate benefits for the company from the introduction of corporate social responsibility are the creation of a stable business environment, reduced operational risks, increased financial performance and sales, increased productivity, reduced costs, market expansion etc. In Ukraine, the development of corporate social responsibility began with the establishment of a market economy. In the early 90's of 20th century, domestic businessmen began to form an understanding of the need for their participation on a voluntary basis in solving social and environmental problems. Responsible business conduct necessitates the preparation of a public report on the business activity results. Social reporting involves the disclosure of information about both positive and negative results of economic, social, environmental activities of the company. Recently, companies have been preparing not only financial statements but also social statements. Social (non-financial) reporting is becoming an integral part of corporate culture, and the management of corporate social responsibility programs in commercial organizations focused on sustainable development contributes to the balanced social and environmental development of society. Formation and development of domestic socially responsible business should be based on further development of the fundamental institutional foundations necessary for its effective functioning.
Keywords: Corporate social responsibility; company social reporting; socially responsible business.